The Ethical Implications of Doping in Sports: Analysing the Issues of Strict Liability, Unfair Advantage, and Athlete Age - Reynisdóttir, Elín Lára (Πανεπιστήμιο Πελοποννήσου, 2025)
A narrative literature analysis of the ethical implications of doping in sports with a focus on the issues of strict liability, unfair advantage, and athlete age.
Keywords: Ντόπινγκ στον αθλητισμό; Ντόπινγκ στον αθλητισμό - Ηθική; Αναβολικά στεροειδή; Ντόπινγκ στον αθλητισμό - Δίκαιο και νομοθεσία; Doping in sports; Doping in sports - Ethics; Anabolic steroids; Doping in sports - Law and legislation; Sports ethics; Doping; Anti-doping; WADA; Strict liability; Unfair advantage; Athlete age